ADP ribosylation factor 1 facilitates spread of wheat dwarf virus in its insect vector. (2nd June 2019) - Wang, Hui; Liu, Yan; Zhang, Lu; Kundu, Jiban Kumar; Liu, Wenwen; Wang, Xifeng
Abstract: Many plant viruses are vectored by insects in a persistent circulative manner. The insect gut and salivary gland are important barriers limiting virus spread, but the mechanisms by which viruses are able to cross the gut escape barriers of the insect remain largely unknown. Wheat dwarf virus (WDV), transmitted by Psammotettix alienus in a persistent, circulative, and nonpropagative manner, causes the most economically important virus disease in wheat. In this study, ADP ribosylation factor 1 (ARF1) was found to interact with the coat protein of WDV in a yeast two‐hybrid, pull‐down assay and to colocalise with virions in the gut and salivary glands of P . alienus . When transcription of ARF1 was suppressed by RNA interference, the WDV titre decreased in the haemolymph and salivary glands, and transmission efficiency decreased, but titre in the gut did not differ from that of the control. These data suggest that ARF1 of P . alienus binds to the WDV virion and helps virus spread from gut to haemolymph. Our study provides direct experimental evidence that WDV can use the existing membrane trafficking mechanism to aid its spread within the insect vector. This first analysis of the molecular interaction between WDV and its vector P . alienus contributes to understanding the mechanisms involved in circulative transmission of the virus by the leafhopper vector.